Presbiopi pada Kelainan Refraksi - A. Soemarsono, A. Soemarsono (Universitas Gadjah Mada, 1986)
Presbyopia is a problem of old people. Usually asthenopic symptoms begin when the patients approach 40 years old. Refraction anomalies of hypermetropia and myopia influence directly the measure of reading spectacles, so that both these anomalies influence the possibility of asthenopic symptoms. Data from OutÃ¢â¬Â¢Patient Department of Ophthalmology, Dr. Sardjito Hospital, during 6 months were 92 presbyopicÃ¢â¬Â¢emmetropic, 15 presbyopic-myopic, and 75 presbyopic-hypermetropic. The asthenopic symptoms which excite patients to go for medical consultation were not in conformity with the theory concerning asthenopic symptoms. Key Words: presbyopia emmetropia Ã¢â¬â hypermetropia Ã¢â¬â myopia Ã¢â¬â asthenopia